IDENTIFIKASI FUNGI MIKORIZA ARBUSKULA PADA AREAL TANAMAN PERKEBUNAN DAN HORTIKULTURA DI DESA PEMO KELIMUTU - Mardiah Sarah; Donatus Rendo (Agriculture Faculty of Flores University, 2022)
Arbuscular mycorrhiza fungi (FMA) can be found in almost all types of soil. FMA symbiosis can increase plant growth, water absorption, and nutrients such as nitrogen, phosphorus, and other micronutrients. It also can increase resistance to water stress, reduce the level of pathogenic attacks and increase growth booster hormones. The purpose of this study was to identify the type of FMA in several areas of plantation and horticultural crops in Pemo Village. The results showed that a total of 1004 spores were found consisting of two types of FMA, namely the genus of glomus as many as 788 spores, and 216 spores from the genus acaulospora. The planting area that has the highest number of spores is horticultural planting, which is 336 spores. Characteristics of dominant dominant spores of oval and brown.